Investigation of heavy metals on water quality and sediment: A case study Bireuen, Aceh Utara and Lhokseumawe City - Mahidin Mahidin; M. Zaki; Asri Gani; Mariana Mariana; M. Irham; Zahratul Idami; Erdiwansyah Erdiwansyah; Ali Afwanudin; Ali Akbar (Jurnal Kimia Valensi, 2020)
Environmental pollution around the world in the last 10 years has continued to increase with increasing industrial growth. Environmental pollution has reduced the availability of clean water. Clean water is the main thing for all living things on this earth. Therefore, environmental pollution that occurs in the clean water crisis must be handled as soon as possible and reduced by various effective policies. The main focus of this research is to analyze heavy metal pollution on the surface of the water, clean water, and sediments caused by industrial activities. This research is a field study by taking samples directly at the location and then analyzing them in the laboratory. The results of the analysis showed that the highest heavy metal Fe on the water surface was found in Bireuen Regency by 0.28% compared to Lhokseumawe City with 0.0029% and Aceh Utara 0.0029%. Meanwhile, the highest heavy metals contained in clean water were recorded in Bireuen and Lhokseumawe City at 0.007% and 0.0064%, respectively. The results of the heavy metal analysis in the highest sediment were found in North Aceh at 42.93% compared to 8.02% and 18.12% for Bireuen and Lhokseumawe. Overall, the analysis carried out in this study shows that the surface water, clean water, and sediments have been contaminated by heavy metals. Meanwhile, the quality standard for surface water is 0.3 mg/l, net ai is 1.0 mg/l, and sediment is 20bj.